The level of asynchronous online discussion (AOD) usage among undergraduates - Mohd Haris, Noor Farah Shahida; Mahmud, Rosnaini; Wong, Su Luan (IDOSI Publications, 2014)
This paper describes the degree to which undergraduates use asynchronous online discussion (AOD) in the learning process. This study was carried out on academic semester 1 2012/2013 in Universiti Putra Malaysia. The design of the study was in the form of a survey using a five point Likert scale questionnaire. The questionnaire consisted of 13 items that were divided into two sub-sections to measure the AOD usage in terms of volume and frequency. Findings show that, majority of the undergraduates self-reported moderate level of AOD usage.